2020
DOI: 10.1038/s41598-020-63565-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA survey captures patterns of fish and invertebrate diversity across a tropical seascape

Abstract: Accurate, rapid, and comprehensive biodiversity assessments are critical for investigating ecological processes and supporting conservation efforts. Environmental DNA (eDNA) surveys show promise as a way to effectively characterize fine-scale patterns of community composition. We tested whether a single PCR survey of eDNA in seawater using a broad metazoan primer could identify differences in community composition between five adjacent habitats at 19 sites across a tropical Caribbean bay in Panama. We paired t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 67 publications
6
55
0
Order By: Relevance
“…The results of this study suggest the potential of the molecular approach for biodiversity assessments of remote ecosystems. eDNA sequencing was sensitive enough to detect distinct communities between adjacent habitat types, as was previously shown for shallow water tropical habitats (Nguyen et al, 2020). Sessile taxa detected on nodules with eDNA were broadly consistent with previous inventories of species associated with this abyssal substrate type.…”
supporting
confidence: 86%
“…The results of this study suggest the potential of the molecular approach for biodiversity assessments of remote ecosystems. eDNA sequencing was sensitive enough to detect distinct communities between adjacent habitat types, as was previously shown for shallow water tropical habitats (Nguyen et al, 2020). Sessile taxa detected on nodules with eDNA were broadly consistent with previous inventories of species associated with this abyssal substrate type.…”
supporting
confidence: 86%
“…However, Jeunen et al (2019) demonstrated that eDNA was able to discriminate diverse marine habitats within a small spatial scale subject to tidal and water currents. Indeed, some studies have already shown that eDNA surveys are able to detect fine-scale community composition patterns in heterogeneous aquatic habitats (Port et al, 2016;O'Donnell et al, 2017;Pont et al, 2018;Bakker et al, 2019;Stat et al, 2019;Nguyen et al, 2020;Oka et al, 2020). In our study, the residency time and degradation rate of nsDNA in the sponge tissues is an important factor that can hamper the detection of community patterns.…”
Section: Discussionmentioning
confidence: 80%
“…Some recent studies have pointed out the differences between eDNA metabarcoding methods and visual or capture methods (Tkachenko et al, 2016;Yamamoto et al, 2017;Fujii et al, 2019;Stat et al, 2019). The main advantages of metabarcoding rely on its time efficiency (Yamamoto et al, 2017;Nguyen et al, 2020), its detection capability of eDNA signatures of fishes that cannot be observed during visual surveys (Nguyen et al, 2020) and the dispensable need of taxonomic expertise (DiBattista et al, 2017). In this sense, censuses made by different observers may not be comparable, while results from eDNA are more objective and, particularly, better suited for archiving and future reanalyses (the sequences remain in databases, visual observations are hardly archivable).…”
Section: Comparisons With Visual Census Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above six case studies conducted in various marine environments, MiFish eDNA metabarcoding has been applied to biodiversity monitoring at two coastal areas of eastern Java and Sulawesi Sea, Indonesia (Masengi et al 2019;Andriyono et al 2019); port and urban canal area in Osaka Bay, central Japan (Kamimura et al 2018); Innoshima, Seto Inland Sea, Japan (Sakamoto 2019); coastal waters off Zhoushan, China (Chen et al 2019(Chen et al , 2020; a harbor at Sloehaven, the Netherlands (Hoorn and Gittenberger 2019); Gulf of St. Laurence Bay, Canada (Afzali et al 2020); Caribbean bay in Panama (Nguyen et al 2020); and coastal waters along the South Africa by members of the von der Heyden Lab (https ://www.vonde rheyd enlab .com/envir onmen tal-dna-and-metab arcod ing.html).…”
Section: Marine Fish Communitymentioning
confidence: 99%